Costos privados y costos sociales - Jürgensen, Harald (1965)
The individual economic units, are the sources of trade and service of an economic region and part of the total cost to supply same is upheld by third parties, the latter non-participants in the production process. This being the motive for the numerous problems made manifest in the differentiation between social production costs and private production costs. He endeavours to establish his definition by means of a synthesis of the basic concepts of LAUSCHMANN and analyzes the possibilities of the causal relations which he classifies and of which he considers of important only three, to which he limits his analysis. Dealing with the most important, he concentrates on the analysis of between one and other, with view to determining how they may be registered, measured and eliminated or neutralized by economic means. The matter is illustrated by examples taken from the German Federal Republic experience.